'Another World Just out of Sight': Remembering or Imagining Utopia in Emily St. John Mandel's Station Eleven. Issue 2 (10th August 2018) - Leggatt, Matthew
At the heart of Station Eleven lies a tension between remembering and imagining. Whereas most post-apocalyptic texts value their contemporary society by generating a sense of 'nostalgia' for the present, St. John Mandel's novel places its emphasis on the imaginary and utopian possibilities that could accompany disaster. In the novel, a host of now useless objects become aesthetic links to the past, reminders collected by Clark in the Museum of Civilization; the Travelling Symphony's productions of Shakespeare plays act as a way of remembering; and the patriarchal violence enacted by the Prophet offers an unpleasant re -enactment of the religious fanaticism that has punctuated history. But, whereas the objects and beliefs of the past provide a constant draw back into a nostalgic appreciation for a life that can never be recaptured, it is Miranda's self-published comic book, Dr. Eleven, that suggests the importance and primacy of imagination over remembrance in the wastelands of the future. Just as the comic offers Miranda an escape from the domination of the male figures in her life – first boyfriend Pablo, then actor-husband Arthur Leander – before the Georgia Flu pandemic, the comic's survival in the aftermath is what gives the novel its hopeful aspect. This article explores the way in which Station Eleven offers hope not through a rekindling of an exhausted past, but in a new imagined future in which the traditional lines and boundaries of relationships, ideals, identity, and community can be redrawn in 'another world just out of sight' (Mandel, 2015: 333 ).